Five years of advances in electrochemical analysis of protein biomarkers in lung cancer: a systematic review - Regiart, Daniel Matias Gaston (2024)
Lung cancer is the leading cause of cancer death in both men and women. Itrepresents a public health problem that must be addressed through the earlydetection of specific biomarkers and effective treatment. To address this criticalissue, it is imperative to implement effective methodologies for specificbiomarker detection of lung cancer in real clinical samples. Electrochemicalmethods, including microfluidic devices and biosensors, can obtain robust resultsthat reduce time, cost, and assay complexity. This comprehensive review willexplore specific studies, methodologies, and detection limits and contribute tothe depth of the discussion, making it a valuable resource for researchers andclinicians interested in lung cancer diagnosis.